Effect of ultrasound-guided internal branch of superior laryngeal nerve block on postoperative sore throat induced by a NIM-EMG-ETT: study protocol for a double-blinded randomized controlled trial - Xi Liu; Aizhong Wang; Zhihua Jiao; Jun Yao; Xiaoxiao Chen; Limin Luo; Hui Zhang (Trials)
Abstract Background Postoperative sore throat (POST) is a common complaint after general anaesthesia. The prevalence of POST caused by a neural integrity monitor electromyography endotracheal tube (NIM-EMG-ETT) is high. This study aimed to determine whether ultrasound-guided internal branch of superior laryngeal nerve block (iSLNB) could alleviate POST associated with a NIM-EMG-ETT. Methods This randomized controlled trial plans to enroll 182 patients scheduled to undergo general anaesthesia with a NIM-EMG-ETT. Patients will be randomly allocated into the iSLNB group or the control group according to randomized numbers generated by Excel. After induction, patients in the iSLNB group will undergo ultrasound-guided iSLNB with ropivacaine, and patients in the control group will undergo the same procedure with normal saline. The prevalence, severity, visual analogue scale score of POST, and postoperative acoustic analysis will be recorded. Discussion To the best of our knowledge, this is the first study to evaluate the effect of ultrasound-guided iSLNB with ropivacaine on the mitigation of POST induced by NIM-EMG-ETT. Our study will provide clinical answers to alleviate POST induced by NIM-EMG-ETT. The results of this study may provide a safe method to prevent POST caused by NIM-EMG-ETT. Trial registration Chinese Clinical Trial Registry, ChiCTR2300076393. Registered on October 24, 2023, http://www.chictr.org.cn/index.aspx .